UPAYA PEMERINTAH KABUPATEN INDRAGIRI HULU DALAM PENGENTASAN ANAK PUTUS SEKOLAH (STUDI KASUS SEKOLAH DASAR DI KECAMATAN BATANG CENAKU TAHUN 2011-2012) - Rio Kusbowo; M.Y.Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The problems of school dropouts is like dynamite for Indonesian that never be ended because the number of school dropout rates increases each year, as happened in Indragiri Hulu, especially in BatangCenaku. The numbers of school dropouts in elementary level amounted to 66 students from 4856 students in 2011 while in 2012 the numbers of schools dropouts increased to 188 students from 4951 students.A negative impact for the Indragiri Hulu if the problem can not be solved by the government of Indragiri Hulu. So the researcher formulates what factors are the causes of school dropouts at the elementary level in BatangCenaku? How are the efforts of local government of educational sector in the reduction of school dropouts in BatangCenaku?This is a qualitative research. The location of this study is at the office of District Education of Indragiri Hulu, in Batang Cenaku. In collecting the data the researcher used purposive sampling technique. Purposive sampling is a technique that usedparticular consideration in collecting the data sample, for example, the person considered as most knowledgeable about what to expect, so it will be easier for researcher to explore objects and social situation investigated. To get the data, the researcher used the following methods: observation, interviews, and documentation. To describe the issues discussed, analyzing the data is needed to do.According to the finding research the causes of school dropouts are the economy, family, school, peers, and academic ability. The efforts of the Government of Indragiri Hulu appropriate toauthority possessed by the local government issued a policy of reduction of school dropouts in the form of movement compulsory education of villages based including updating data dropouts or no schooling children, socialization to the people, Assistance Fund, Optimizing Scholarship Education for poor people, and Education Pack Assistance Program.Keywords: Authority, Dropouts, Education